Thermally activated escape rate for the Brownian motion of a fixed axis rotator in an asymmetrical double-well potential for all values of the dissipation - COFFEY, WILLIAM THOMAS; KALYMYKOV, YURI PETROVICH; TITOV, SERGEY (American Institute of Physics, 2005)
The Kramers theory of the escape rate of a Brownian particle from a potential well as extended by Mel'nikov and Meshkov, [J. Chem. Phys. 85, 1018 (1986)] is used to evaluate the relaxation times and the dynamic susceptibility for the rotational Brownian motion of fixed axis rotators in an asymmetric double-well potential. An expression for the escape rate valid for all values of the dissipation including the very low damping (VLD), very high damping (VHD), and crossover regimes is derived. It is shown that this expression provides a good asymptotic estimate of the inverse of the smallest nonvanishing eigenvalue lambda1 of the underlying Fokker-Planck operator calculated by using the matrix-continued fraction method. For low barriers, where the Mel'nikov and Meshkov approach is not applicable, analytic equations for the correlation time tau|| of the longitudinal dipole correlation function in the VLD and VHD limits are derived and a simple extrapolating equation valid for all values of the damping is proposed.
PUBLISHED
Keywords: Electronic & Electrical Engineering